Conventional and ultrasound-assisted bioaccumulation of azo dye Indosol Black NF-1200 by kefir biomass - Mutlu, Hatice; Apar, Dilek Kilic (ELSEVIER SCIENCE INC, 2021)
In the present work, conventional and ultrasound-assisted bioaccumulation of direct azo dye Indosol Black NF-1200 (IB) by active kefir biomass was investigated. The kefir biomass was characterised by scanning electron microscopy, Fourier transform infrared spectroscopy and Brunauer-Emmett-Teller analyses. Batch mode experiments were carried out to study the effect of experimental factors such as pH, initial dye concentration and temperature on IB dye bioaccumulation. Both in conventional and ultrasound-assisted bioaccumulation the dye removal percentage increased with the decrease in pH and initial dye concentration and with the increase in temperature. Higher dye removal efficiencies were achieved, and the equilibrium times significantly decreased in bioaccumulation processes assisted by ultrasound. The enhancement effect of ultrasound was more significant at high pHs, high dye concentrations and low temperatures. Dye removals of 73% and 96% were obtained at pH 2, 25 degrees C and 50 mg L-1 initial dye concentration for conventional and ultrasound-assisted bioaccumulation in which the equilibrium was reached within 180 and 30 min, respectively. The kinetic data fitted well with pseudo-first-order and pseudo-second-order kinetic models for conventional and ultrasound-assisted bioaccumulation, respectively. Equilibrium data of both processes fitted well with the Langmuir isotherm model. Ultrasound-assisted bioaccumulation of a dye was investigated for the first time in this study. The results reveal that ultrasound can be used as a powerful option for the improvement of bioaccumulation processes and showed that kefir biomass could be used effectively for the removal of direct dyes.
Keywords: Azo dye; Bioaccumulation; Kefir biomass; Modelling; Ultrasound; AQUEOUS-SOLUTION; METHYLENE-BLUE; TEXTILE DYE; ADSORPTION; REMOVAL; CONSORTIUM; RED; Engineering; Water Resources